Analisis Pemanfaatan Aplikasi E-Commerce Dalam Meningkatkan Penjualan Pada UMKM Sektor Kuliner di Kota Makassar - Ika Putri, Hindong; Rijal, Abdul; Afiah, Nur (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2024)
This research aims to analyze the use of e-commerce applications in increasing sales in MSMEs in the Culinary Sector in Makassar City. The variables of this research are utilization of e-commerce applications as the independent variable (X) and sales as the dependent variable (Y) which is measured by sales growth. The population of this research is sales reports for MSMEs in the Culinary Sector in Makassar City, while the sample is sales reports for 2019-2023 for MSMEs in the Culinary Sector in Makassar City which were taken using the purpose sampling technique. Data collection was carried out using documentation and interviews. Data analysis was carried out using descriptive quantitatif methods. The results of this research show that e-commerce applications can increase sales in the Culinary Sector MSMEs in Makassar City if they are utilized optimally by providing promotions for consumers.